2022
DOI: 10.1186/s43046-022-00129-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of treatment interruptions and outcomes in cancer patients undergoing radiotherapy during the first wave of COVID-19 pandemic in a tertiary care institute

Abstract: Introduction COVID-19 patients with cancer had poorer outcomes due to immunosuppression during cancer care, poor general condition, and other comorbidities. The study was conducted to present the real-world analysis of the effect of treatment interruptions on the outcomes of patients treated with radiation therapy during the first wave of the COVID-19 pandemic in a tertiary care institute in India. Materials and methods The study is a retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…A series of effort had been exerted to stop the spread of COVID-19 worldwide, although these policies could disturb normal medical behavior. Hence, this finding is in line with a survey in the Netherlands whereby chemotherapy, immunotherapy, or radiotherapy for many cancer patients was postponed or cancelled (Guven et al, 2020a;van der Veldt et al, 2021;Barik et al, 2022). However, patients' fear of COVID-19 grew as a result of the delay in treatment.…”
Section: Discussionsupporting
confidence: 83%
“…A series of effort had been exerted to stop the spread of COVID-19 worldwide, although these policies could disturb normal medical behavior. Hence, this finding is in line with a survey in the Netherlands whereby chemotherapy, immunotherapy, or radiotherapy for many cancer patients was postponed or cancelled (Guven et al, 2020a;van der Veldt et al, 2021;Barik et al, 2022). However, patients' fear of COVID-19 grew as a result of the delay in treatment.…”
Section: Discussionsupporting
confidence: 83%
“…It was reported by other investigators that patients receiving recent cancer therapy may have better outcome to COVID-19, [ 27 ] but larger studies and other registry data showed recent cancer treatment was associated with adverse outcomes. [ 22 , 28 ] This discrepancy may be explained by the heterogeneity the diseases itself, the treatment regimens used, and their effects on the immune system and other organs. Metastatic disease status was associated with increased risk compared with localized disease in cancer patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Interruption of chemotherapy or radiotherapy has been shown to negatively affect outcome in several studies. [ 9 , 28 ] In a large U.S. study of more than 500,000 patients with cancer or no cancer, patients with cancer had worse outcomes. Patients with metastatic disease or receiving recent cancer treatment had worse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Disruptions in radiotherapy, however, are inevitable for several unavoidable factors, such as public holidays ( 37 ) (the largest share, about 39-46%), machine failures, patient compliance, and adverse effects of treatment ( 38 ). Similarly, because of the pandemic of Corona Virus Disease 2019, confirmed positive patients had longer treatment interruptions, which led to fewer patients completing radiotherapy, thus increasing local disease progression ( 39 ).…”
Section: Interruption Of Radiotherapymentioning
confidence: 99%